2003
DOI: 10.1038/sj.onc.1206792
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Bim-EL by Erk1/2 on serine 69 promotes its degradation via the proteasome pathway and regulates its proapoptotic function

Abstract: Bim is a proapoptotic member of the Bcl-2 family that shares only the BH3 domain with this family. Three Bim proteins Bim-EL, Bim-L and Bim-S are synthesized from the same transcript. We report here that Bim-EL when phosphorylated by Erk1/2 is rapidly degraded via the proteasome pathway. Using different cellular models we evidence that serine 69 is both necessary and sufficient for Erk1/2-mediated phosphorylation and degradation of Bim-EL. In K562 cells, Phorbol 12-myristate 13-acetate activates Erk1/2 and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

51
490
3
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(546 citation statements)
references
References 25 publications
51
490
3
2
Order By: Relevance
“…As BimEL degradation occurred concomitantly with phosphorylation, we examined two phosphorylation sites on BimEL previously shown to regulate proteolysis. Erk 1 and 2 were shown to phosphorylate BimEL on S69 10,12,18 and promote degradation and phosphorylation on S93/94/98 has been shown to induce degradation through the Skp1-Cullin1-F-Box (SCF) complex. 20 In order to assess the importance of these sites for BimEL degradation in mitosis, phosphospecific antibodies were used to monitor these modifications during mitosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As BimEL degradation occurred concomitantly with phosphorylation, we examined two phosphorylation sites on BimEL previously shown to regulate proteolysis. Erk 1 and 2 were shown to phosphorylate BimEL on S69 10,12,18 and promote degradation and phosphorylation on S93/94/98 has been shown to induce degradation through the Skp1-Cullin1-F-Box (SCF) complex. 20 In order to assess the importance of these sites for BimEL degradation in mitosis, phosphospecific antibodies were used to monitor these modifications during mitosis.…”
Section: Resultsmentioning
confidence: 99%
“…4,7,8 Post-transcriptional mechanisms that have been shown to control Bim expression levels include both mRNA stability 9 and protein stability. [10][11][12] Signaling downstream of receptor tyrosine kinases (RTKs) including epidermal growth factor receptor induce the proteasomal degradation of Bim. [13][14][15][16] There are three splice variants of Bim: BimEL, BimL and BimS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exon 3 includes an ERK1/2 docking domain (FSF) and ERK1/2 phosphorylation sites, including Ser69. [29][30][31]33 The presence of exon 3 in Bima1, Bimb1 and Bimb2 also correlates with their ERK1/2-dependent phosphorylation in vivo. 33 ERK1/2-dependent phosphorylation of Bim EL targets it for proteasomal degradation and may prevent binding to Bax.…”
Section: Bim As a Sensor Of Survival Factors And Trophic Supportmentioning
confidence: 92%
“…Phosphorylation of BIM by ERK was reported to be critical for the antiapoptotic activity of this kinase. [56][57][58][59][60] However, a recent study has shown that ERK-mediated direct phosphorylation of BIM does not have a major role in the control of the proapoptotic activity of this BH3-only protein within the whole animal. 61 Both BIM and BMF were shown to be sequestered by binding to elements of the cytoskeleton, thereby restraining their pro-apoptotic activity.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%